Black Holes with Abelian and Non-Abelian Charges and Their Impact on Matter Accretion Flows - Cruz-Marin, N (Academic Press, 2023)
In this paper, we study the black hole spacetime structure of a model consisting of the standard Maxwell theory and a p-power-Yang–Mills term. This non-linear contribution introduces a non-Abelian charge into the global solution, resulting in a modified structure of the standard Reissner–Nordström black hole. Specifically, we focus on the model with p=1/2, which gives rise to a new type of modified Reissner–Nordström black hole. For this class of black holes, we compute the event horizon, the innermost stable circular orbit, and the conditions to preserve the weak cosmic censorship conjecture. The latter condition sets a well-established relation between the electric and the Yang–Mills charges. As a first astrophysical implication, the accretion properties of spherical steady flows around this new modified Reissner–Nordström black hole are investigated in detail. Concretely, we compute the critical radius that establishes the condition for having stable transonic flow in terms of the local sound speed and the involved charges. Extensive numerical examples of how the Yang–Mills charge affects the accretion process of an isothermal fluid in comparison to the standard Reissner–Nordström and Schwarzschild black holes are displayed. Finally, analytical solutions in the fully relativistic regime, along with numerical computations, of the mass accretion rate for a polytropic fluid in terms of the electric and Yang–Mills charges are obtained. As a main result, the mass accretion rate efficiency is considerably improved, with respect to the standard Reissner–Nordström and Schwarzschild solutions, for negative values of the Yang–Mills charge. © 2023 The Authors